Pelaksanaan Pengembangan Kapasitas Kelembagaan Pemerintahan Daerah (Studi di Bagian Organisasi Sekretariat Daerah Pemerintah Kabupaten Malang) - Marliawati, Desy (Jurnal Administrasi Publik, 2013)
Abstract: Implementation Of The Development Of The Institutional Capacity Of Local Government : This institutional capacity development is the Government's efforts in improving the organisation of Malang Regency area devices and improve institutional performance to carry out the administration of local government that is effective and efficient. Research purposes are to determine, describe and analyse the implementation of the development of the institutional capacity of local government and the factors that influence the implementation of institutional capacity development in the area of Secretariat Government of Malang Regency. This study used descriptive study with qualitative approach. Implementation of the Government's institutional capacity development of Malang Regency has been running quite effectively, this is evidenced by the implementation is already done for 1 year 1 times continuously, as well as the components of institutional capacity development that have been carried out. However, there are still shortcomings, namely lack of other facilities and infrastructure as well as a lack of understanding of the established work procedures. Keywords: Capacity Building, Institutions, Local Government.   Abstrak: Pelaksanaan Pengembangan Kapasitas Kelembagaan Pemerintahan Daerah : Pengembangan  kapasitas kelembagaan merupakan upaya pemerintah Kabupaten Malang dalam meningkatkan organisasi perangkat daerah serta memperbaiki kinerja kelembagaan untuk melaksanakan administrasi pemerintahan daerah yang efektif dan efisien. Tujuan penelitian ini adalah mengetahui, mendeskripsikan dan menganalisis pelaksanaan pengembangan kapasitas kelembagaan pemerintahan daerah serta Faktor-Faktor yang mempengaruhi pelaksanaan pengembangan kapasitas kelembagaan di Bagian Organisasi Sekretariat Daerah Pemerintah Kabupaten Malang. Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan  kualitatif. Pelaksanaan pengembangan kapasitas kelembagaan Pemerintah Kabupaten Malang sudah berjalan cukup efektif, hal ini dibuktikan dengan pelaksanaanya yang sudah dilakukan selama 1 tahun 1 kali secara terus-menerus, serta komponen-komponen dari pengembangan kapasitas kelembagaan lain yang telah dilakukan. Namun masih terdapat kekurangan yaitu  kurang memadainya sarana dan prasarana yang dimilki dan juga kurangnya pemahaman terhadap prosedur kerja yang telah ditetapkan.   Kata Kunci: Pengembangan Kapasitas, Kelembagaan, Pemerintah Daerah